Lignin degradation using lignolytic enzymes - Ayixiamuguli, Nueraimaiti (2016)
Lignin is the only plant biomass that contains aromatic groups in its structure and can provide a wide range of low molecular weight aromatic chemicals if its depolymerisation can be achieved successfully. Currently, lignin is mainly produced as a waste by-product by the paper and pulp industry and biorefineries. Therefore, the transformation of the phenolic-rich lignin into value added aromatic platform chemicals can be regarded of primary concern to improve the economic profitability of biorefining. Moreover, being a renewable resource, the consumption of fossil fuels will be reduced if lignin can be utilised efficiently. Between chemical degradation and enzymatic degradation, the latter could be a more sustainable method to break down lignin due to its enhanced substrate specificity and ability to preserve the aromatic ring structure compared with chemical processing. Therefore, laccase from Trametes versicolor (LTV), lignin peroxidase (LiP) and manganese peroxidase (MnP) were studied to determine the scope to depolymerise both water-soluble and insoluble lignins nder mild reaction conditions. The enzymatic activity and stability of all three enzymes was investigated and optimum assay conditions were achieved. LTV was found to be the most stable enzyme as it maintained 55 % of its activity at least for the first 6 h at 30 °C whereas LiP was deactivated after 2 h at 25 °C, and MnP was deactivated after 1 h at 28 °C. However, LTV stability decreased at higher temperatures during the oxidation of 2,2’-azino-bis (3- ethylbenthiazoline-6-sulphonic acid (ABTS). One of the non-phenolic lignin model compounds, veratryl alcohol, was oxidised by LTV in the presence of ABTS, thus confirming the published data. The enzymatic degradation of Organosolv lignin (OSL) by LTV resulted in the formation of 2,6-dimethoxy-1,4-benzoquinone (DBQ). The OSL degradation by LTV was not improved by ethanol addition as a co-solvent although ethanol could stabilise LTV at 40 % (v/v). LTV catalysed the degradation of Kraft lignin although it indicated little effect on lignosulphonates. Lastly, the effect of varying the concentrations of 92 ionic liquids (ILs) and their equivalent metal salts on LTV activity was investigated to find a suitable co-solvent to improve the poor mass transfer in OSL degradation. The study showed that 62 ILs were laccase compatible at an IL concentration of 6 % (w/v) and more than 50 % laccase activity was retained in 18 ionic liquids up to 10 % (w/v), and 80 % (v/v) of dioctyl sulfosuccinate quaternary ammonium salt, [N4,4,4,4][AOT]. However, there was a progressive loss of activity when the concentrations of the ILs increased. Further study on the enzymatic degradation of ILs-pre-treated OSL is currently ongoing in our research group so that the decomposition of water-insoluble lignin will be understood more comprehensively.